Serosurvey of rickettsia spp. In cats from a Brazilian spotted fever-endemic area - Mendes, Juliana Cristina Rebonato; Kmetiuk, Louise Bach; Martins, Camila Marinelli; Canavessi, Aurea Maria Oliveira; Jimenez, Tatiana; Pellizzaro, Maysa [UNESP]; Martins, Thiago Fernandes [UNESP]; Morikawa, Vivien Midori; Dos Santos, Andrea Pires; Labruna, Marcelo Bahia; Biondo, Alexander Welker (FapUNIFESP (SciELO), 2019)
Rickettsia spp. bacteria are responsible for tick-borne diseases worldwide, mostly maintained by rickettsial amplifiers capybaras in Brazilian endemic areas. The campus of the University of São Paulo, in southeastern Brazil, is an area endemic for Brazilian spotted fever (BSF), with high density of capybaras and Amblyomma spp., along with confirmed human cases. Besides capybaras, the university has also an in-campus high population of sheltered and free-roaming cats. Accordingly, the aim of this study was to determine the prevalence and characteristics associated with Rickettsia rickettsii, Rickettsia parkeri and Rickettsia felis exposure among cats in a BSF-endemic area. Out of 51 cats sampled, 23/35 shelter (65.7%) and 5/16 free-roaming (31.2%) were positive (titers ≥ 64) for at least one Rickettsia species. Ticks species were present in 3/16 free-roaming cats (18.8%), consisting of Amblyomma spp., nymphs of Amblyomma sculptum and adult Rhipicephalus sanguineus sensu lato. Despite sharing the capybaras environment, the seropositivity among the free-roaming and shelter cats was lower than owned cats in other endemic areas. Whether equally or less exposed to rickettsial infection, compared with owned cats in endemic areas, free-roaming and shelter cats may be used as environmental sentinels for human exposure to rickettsiae in such areas.
Soroprevalência de Rickettsia spp. Em gatos de uma área endêmica para a Febre Maculosa Brasileira
Keywords: Brazilian spotted fever; Rickettsia parkeri; Rickettsia rickettsii